2022
DOI: 10.1186/s12879-022-07041-x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis, epidemiological changes during the SARS-CoV-2 pandemic

Abstract: Background Bronchiolitis is the most common viral infection of the lower respiratory tract in infants under 2 years of age. The aim of this study was to analyze and compare the seasonal bronchiolitis peaks before and during the SARS-CoV-2 pandemic. Methods Descriptive, prospective, and observational study. Patients with severe bronchiolitis admitted to the Pediatric Intensive Care Unit (PICU) of a referral tertiary hospital between September 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 41 publications
(30 reference statements)
6
49
1
4
Order By: Relevance
“…The score included the child’s color, respiratory rate, presence of wheeze, use of accessory muscles, mental status, and oxygen saturation, and each variable ranges from 0 to 2. Thus, CRS total score ranges from 0 to 12 and defines into three categories: Mild (<3), Moderate ( 4 7 ), and Severe ( 8 12 ) ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…The score included the child’s color, respiratory rate, presence of wheeze, use of accessory muscles, mental status, and oxygen saturation, and each variable ranges from 0 to 2. Thus, CRS total score ranges from 0 to 12 and defines into three categories: Mild (<3), Moderate ( 4 7 ), and Severe ( 8 12 ) ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the last 2 years, public health measures aimed at controlling the spread of SARS-CoV-2, such as stay-at-home orders and social distancing, have altered the epidemiology and seasonality of other respiratory viruses [ 20 , 21 ]. Some studies showed a drastic reduction in the number of hospitalizations and a reduction in the length of hospital stay in children with respiratory diseases [ 22 , 23 ]. Moreover, a drop in the total number of pediatric consultations was reported during the 2020 lockdown both in Italy and in Finland [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also in Finland, a rapid decrease in RSV cases was observed in 2020 [ 25 ]. A study conducted in Spain during the pandemic period revealed a very low burden of bronchiolitis, mostly caused by RSV, and a delayed peak compared with previous years [ 22 ]. In Italy, systematic national surveillance of RSV is lacking, therefore very few epidemiological data are available.…”
Section: Introductionmentioning
confidence: 99%
“…Children may be less likely to develop critical illness or concerning symptoms (i.e. viral wheeze) from COVID-19 prompting a medical evaluation [21] , [22] , [23] . Finally, the presence of a non-COVID respiratory viral infection may interfere or block infection from other viruses (including COVID-19) [24] .…”
Section: Discussionmentioning
confidence: 99%